Supply crisis and its effect on agribusiness - Boyano-Fram, Teofilo O.; Claros-Bueno, Edwin J.; Machado-Licona, Jhorquis (EFIM Ediciones, 2022)
The Covid 19 pandemic has wreaked havoc in much of the world in economic, political and social matters, this article aims to analyze the consequences of the pandemic, the supply crisis, the effect on food security and the incidence of ports and the aspects that aggravate it, it was done methodologically by reviewing the existing literature on the subject, a compilation of more than 50 documents is made, to then select a sample and triangulate the information, it has been found that logistical factors such as breakdown of the supply chain, the effects of Covid 19 as a global pandemic that has had an impact on slowing down the production of the manufacturing industry and the closure of ports that mobilize a large part of food supplies, together with little effect on public policies and world ordinances that have gone from speech to action and stop or mitigate the problem of food and therefore become security to alimentary.